Comparison of Marginal Circumference of Two Different Pre-crimped Stainless Steel Crowns for Primary Molars After Re-crimping - Hossein Afshar; Mehdi Ghandehari; Banafsheh Soleimani (Tehran University of Medical Sciences, 2016)
Objectives: It is not clear what type of pre-crimped crown is more successful in achieving greater marginal adaptation following re-crimping. This study aimed to assess the changes in the circumference of 3M ESPE and MIB pre-crimped stainless steel crowns (SSCs) for the primary maxillary and mandibular first and second molars following re-crimping. Materials and Methods: This was an in-vitro, experimental study. Initial photographs were obtained from the margins of 3M and MIB SSCs for the upper and lower primary molars using a digital camera. Crown margins were crimped by applying 0.2N force using 114 and 137 pliers. Post-crimping photographs were also obtained and the changes in crown circumference after crimping were calculated using AutoCad software. The percentage of reduction in the circumference of crowns for each tooth was statistically analyzed based on the type of crown using student t-test. The effect of crown design and the associated teeth on the decreased circumference percentage was statistically analyzed by two-sided ANOVA. Results: The percentage of reduction in lower E SSC circumference was 3.71±0.39% in MIB and 6.29±0.62% in 3M crowns. These values were 3.55±0.55% and 7.15±1.13% for the lower Ds, and 3.95±0.43 and 6.24±0.85% for the upper Ds, respectively. For the upper Es, these values were found to be 3.12±0.65% and 5.14±0.94%, respectively. For each tooth, a significant difference was found between MIB and 3M SSCs in terms of the percentage of reduction in crown circumference following crimping. The magnitude of this reduction was smaller in MIB compared to 3M SSCs (P<0.001). Conclusion: Considering the significant reduction in the marginal circumference of pre-crimped SSCs following re-crimping, it appears that this manipulation must be necessarily performed for MIB and 3M pre-crimped SSCs. By using 3M SSCs, higher marginal adaptation can be achieved following crimping.